2016
DOI: 10.1097/md.0000000000005519
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors of postoperative neurological deterioration after posterior decompression with or without instrumented fusion for thoracic myelopathy

Abstract: The aim of this study was to explore the incidence and risk factors of postoperative neurological deterioration after posterior decompression with or without instrumented fusion for thoracic myelopathy, and hope to provide references in decision-making and surgical planning for both spinal surgeon and thoracic stenosis patients.By retrieving the medical records from January 2001 to November 2015, 168 patients were retrospectively reviewed. According to the occurrence of postoperative neurological deterioration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In patients with severe ossi ed ligamentum avum, the spinal cord was fragile, and minor traction or vibrations during intraoperative removal of the ligamentum avum might lead to severe paralysis. In addition, intraoperative instability caused by extensive laminectomy and an increase in kyphosis after laminectomy had been considered as potential causes for postoperative neurological deterioration (however, there were no cases of kyphosis during the follow-up period of this study) [23]. Last but not least, it has been reported that application of instrumentation after laminectomy dose good to postoperative recovery of the injured spinal cord due to thoracic myelopathy, and prevents re-extension of OLF [24][25].…”
Section: Discussionmentioning
confidence: 70%
“…In patients with severe ossi ed ligamentum avum, the spinal cord was fragile, and minor traction or vibrations during intraoperative removal of the ligamentum avum might lead to severe paralysis. In addition, intraoperative instability caused by extensive laminectomy and an increase in kyphosis after laminectomy had been considered as potential causes for postoperative neurological deterioration (however, there were no cases of kyphosis during the follow-up period of this study) [23]. Last but not least, it has been reported that application of instrumentation after laminectomy dose good to postoperative recovery of the injured spinal cord due to thoracic myelopathy, and prevents re-extension of OLF [24][25].…”
Section: Discussionmentioning
confidence: 70%
“…To decrease the incidence of complications, some surgeons suggested a technique that we should keep a floating fragment adherent to the dura matter [26], but the kind of decompression was not satisfactory when compared with a complete decompression. There was another strategy that increasing the mean arterial pressure could prevent the neurologic deterioration, because Wang et al found that mean arterial pressure less than 81 mmHg was one of risk factors [7]. Besides, to release the immediately neurologic deterioration, glucocorticoid was suggested to ease the inflammation after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 35 studies met the inclusion criteria by reviewing the full-text articles ( Fig. 1) which contained 5 retrospective comparative studies [6][7][8][9][10] and 30 case series [2,4,5, (Table 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…34 suggested that the MAP should be maintained at >81 mmHg to reduce neurological deterioration in thoracic decompression. When all above methods failed to regain signals, the position of the internal fixation instruments should be checked, and local kyphosis of the decompressed segments should be corrected.…”
Section: Factors Influencing Evoked Potentialsmentioning
confidence: 99%